Online Learning Strategy Of MTs Muhammadiyah 1 Taman During Pandemic Covid 19 - Melinda Widyadana Dwi Pramesti (Proceedings of The ICECRS, 2021)
The aim of this study is to find out online learning strategy of MTs Muhammadiyah 1 Taman in the middle of covid 19 pandemic. This research is descriptive qualitative research. Qualitative approach is a research process to understand about social problem by analyzing words and reporting detailed views of information that obtained from interviewees in a social environment.